Using of the Learning Management System on motivation and learning outcomes in the "Merdeka Belajar Kampus Merdeka" Program - Diyah Sukanti Cahyaningsih; Taufiqurrahman Taufiqurrahman; Aditya Galih Sulaksono (Jurnal Penelitian, 2021)
Learning Management System (LMS) is a virtual space where learning activities are carried out remotely. LMS is an innovation in learning that is very useful during the COVID-19 pandemic and MBKM activities to facilitate distance student exchange. LMS should have facilities that are able to encourage learning motivation which will ultimately have implications for learning outcomes. This study examines the effect of using LMS on learning outcomes by placing learning motivation as an intervening variable. The sample of this research is students who use LMS, both MBKM participants and not in the 2020 academic year even. By using path analysis, this research proves that the use of LMS has an effect on student learning motivation, the use of LMS and student learning motivation has a significant effect on learning outcomes, and student learning motivation can be an intervening variable in this research model.